Heuristic and analytic processes in reasoning: An event‐related potential study of belief bias. (19th December 2013) - Banks, Adrian P.; Hope, Christopher
Abstract Human reasoning involves both heuristic and analytic processes. This study of belief bias in relational reasoning investigated whether the two processes occur serially or in parallel. Participants evaluated the validity of problems in which the conclusions were either logically valid or invalid and either believable or unbelievable. Problems in which the conclusions presented a conflict between the logically valid response and the believable response elicited a more positive P3 than problems in which there was no conflict. This shows that P3 is influenced by the interaction of belief and logic rather than either of these factors on its own. These findings indicate that belief and logic influence reasoning at the same time, supporting models in which belief‐based and logical evaluations occur in parallel but not theories in which belief‐based heuristic evaluations precede logical analysis.